Q: How you simplify 2x3 23x?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Rearrange: 4x5 + 6x2 + 6x3 + 9 Group: 2x2 (2x3 + 3) + 3 (2x3 + 3) Simplify to get your answer: (2x2 + 3) (2x3 + 3)

(3^2)^3 is 3^()2x3=3^6

23x - 9x = 14x

It is the inequality: 23x + 4 > 12.

5x + 23x + 10 = 28x + 10( ? ? ? )

Related questions

It is 16y+23x simplified

Rearrange: 4x5 + 6x2 + 6x3 + 9 Group: 2x2 (2x3 + 3) + 3 (2x3 + 3) Simplify to get your answer: (2x2 + 3) (2x3 + 3)

(3^2)^3 is 3^()2x3=3^6

4x-23x = -19

23x - 9x = 14x

It is the inequality: 23x + 4 > 12.

Are those x's or multiplication signs?

5x + 23x + 10 = 28x + 10( ? ? ? )

6x2+23x+20=0x= .7275 and -4.5634Improved Answer:-6x2+23x+20 = (3x+4)(2x+5) when factored

The factors of 23x2 are: 1, 23, x, x2, 23x, and 23x2.

x2 23x equals 0

The answer is 25x + 3.